Local infiltration anaesthesia versus sciatic nerve and adductor canal block for fast-track knee arthroplasty: A randomised controlled clinical trial. Issue 4 (April 2019) - Kastelik, Joanna; Fuchs, Michael; Krämer, Michael; Trauzeddel, Ralf F.; Ertmer, Martin; von Roth, Philipp; Perka, Carsten; Kirschbaum, Stephanie M.; Tafelski, Sascha; Treskatsch, Sascha
Abstract : BACKGROUND: Local infiltration anaesthesia (LIA) was introduced as an innovative analgesic procedure for enhanced recovery after primary total knee arthroplasty (TKA). However, LIA has never been compared with analgesia based on an adductor canal catheter and a single-shot sciatic nerve block. OBJECTIVE: To evaluate two analgesic regimens for TKA comparing mobility, postoperative pain and patient satisfaction. DESIGN: Two-group randomised, controlled clinical trial. SETTING: Charité-Universitätsmedizin Berlin, Campus Charité Mitte, Germany between April and August 2017. PATIENTS: Adults undergoing primary TKA under general anaesthesia were eligible for study participation. Exclusion criteria were heart insufficiency (New York Heart Association class >2), liver insufficiency (Child Pugh Score >B), evidence of diabetic polyneuropathy, severe obesity (BMI > 40 kg m −2 ), chronic opioid therapy for more than 3 months before scheduled surgery and allergy to local anaesthetics. INTERVENTIONS: Nerve block patients group ( n =20) underwent surgery with two ultrasound-guided regional anaesthesia blocks: a single-shot sciatic nerve block with 20 ml of ropivacaine 0.75% combined with an adductor canal block with a catheter placed for less than 4 days with an infusion of ropivacaine 0.2% at a rate of 6 ml h −1 . LIA patients (LIA group, n =20) received LIA of the knee capsule at the end of surgery with 150 ml of ropivacaine 0.2%. MAIN OUTCOME MEASURES: The primary endpoint was postoperative time to patient mobilisation (ability to walk) on the ward. RESULTS: Baseline characteristics were similar in each study group. Patients in both groups were mobilised to walk after TKA in similar time frames (LIA 24.0 h versus nerve block 27.1 h, 95% CI of difference −9.6 to 3.3 h). Maximum postoperative pain scores on exertion were higher in LIA patients with a mean 1.3 of 10 numerical rating scale points (95% CI 0.3 to 2.3, P = 0.010) as were intra-operative opioid requirements (LIA median 107 [IQR 100 to 268] mg versus nerve block median 78 [60 to 98] mg, P < 0.001). Patient satisfaction, postoperative oral morphine-equivalents and resting pain levels were comparable between groups. Anaesthesia induction time was reduced in LIA patients (LIA 10 min versus nerve block 35 min, 95% CI of difference 13 to 38 min, P < 0.001). CONCLUSION: Both analgesic regimens allow early mobilisation after TKA with high patient satisfaction. LIA shortened peri-operative time. Further research is required to optimise especially pain control during the later postoperative period with LIA. CLINICAL TRIAL REGISTRATION: Clinicaltrials.gov identifier NCT03114306.